Front Cover: Metal‐Bonded Redox‐Active Triarylamines and Their Interactions: Synthesis, Structure, and Redox Properties of Paddle‐Wheel Copper Complexes (ChemistryOpen 3/2019). Issue 3 (29th January 2019) - Akintola, Oluseun; Böhme, Michael; Rudolph, Manfred; Buchholz, Axel; Görls, Helmar; Plass, Winfried
Abstract : The Front Cover shows a scene illustrating the need to investigate the properties of building blocks for complex systems to enable the basic design of new functional materials. It shows a model of the investigated paddle‐wheel complexes with copper‐bonded triphenylamines. Both paddle‐wheel units and triarylamine linkers are basic constituents found in several frameworks such as the networks shown in the image. More information can be found in the Full Paper by O. Akintola et al. onpage 266 in Issue 3, 2019 (DOI:10.1002/open.201800243 ).